Impact of land fragmentation and soil fertility on Aus rice producers technical efficiency in Barisal district of Bangladesh (Journal of the Bangladesh Agricultural University, 2016)
This article determines the impact of land fragmentation and soil fertility on Aus rice producers technical efficiency (TE) of Barisal district in Bangladesh. A total of 60 farm households from two villages were selected using stratified random sampling procedure. Detailed input and output data for the Aus were collected in May 2015. Cobb-Douglas stochastic frontier model was used to address this TE. Results indicate that the mean TE was 0.61. Among the four land fragmentation indicators two were found to be statistically significant with anticipated signs. The positive effect of the number of plots on TE implies that variation effect exceeded the management effect and the average distance from plots to homestead indicating loss of time and inconvenience in farming management as well as inefficiencies in input use. The study also used two indicators of soil fertility (i.e., share of highly fertile land and share of not highly fertile land). Between these share of highly fertile land had positive impact on TE in rice productivity. Therefore, the study includes policy implications addressing the structural causes of land fragmentation and developing effective strategies to promote soil conservation.J. Bangladesh Agril. Univ. 14(1): 75-81, June 2016